Bolivia: Los avances sociales y laborales en el periodo de boom económico y los desafíos con el fin de la bonanza - Fernanda Wanderley (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2018)
– At the beginning of the 21st century, Bolivia presented improvements in the indicators of poverty and monetary inequality following the trend of Latin America. The analysis of the evolution of the Unsatisfied Basic Needs Index (NBI) also shows a positive trend. However, significant differences still persist by geographic area - urban and rural - and between departments. The period between 2004 and 2014 was characterized by an exceptional economic bonanza, mainly due to the increase in demand and international prices of raw materials. As of 2014, the fall in the price of tin, hydrocarbons and other raw materials marked the slowdown in the expansive cycle of the international economy and the prices of raw materials and the beginning of a cycle of economic retraction in the region. Considering the historical dependence of the regional economy on the boom and collapse of the prices of natural resources and, consequently, on the negative economic and social effects caused by a strong volatility of our markets, the following questions are imposed: What were the most important factors for the improvement of social indicators in the period of economic boom?, and what policies are needed to sustain the improvement of social indicators and continue to expand the well-being of the Bolivian population? The objective of the document is to present the social advances and the persistent problems to achieve the social well-being of all Bolivians based on the latest available official indicators and secondary studies, and explanations about the factors that affected the social improvements. The document offers a synthesis of the main challenges that the country still faces.
Keywords: I31; I32; I38; I24; J21; J31; 330; Poverty; Inequality; Social protection system; employment; income and salaries; social policies